Water Quality of the Kampar River, Kampar Regency based on Periphyton community structure and WQI-NSF Index - Ken Radityo Gautama; Nur El Fajri; Adriman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The Kampar River received pollutants originated from anthropogenic activities along the river and thus negatively affect the water quality in general. To understand the water quality of the river based on periphyton community structure and WQI-NSF Index, a research was conducted from January to March 2017. There were five (5) sampling points. Water samples were taken 3 times/ week. Water quality parameters measured were temperature, turbidity, transparency, current speed, total suspended solid, depth, pH, DO, BOD5, nitrate, phosphate and types of periphyton present. Results shown that there were 5 classes of periphyton present, namely Cyanophyceae (8 species), Chlorophyceae (16 species), Bacillarophyceae (18 species), Xantophyceae (2 species) and Euglenophyceae (2 species). Water quality parameters are as follows : Temperature 30.3-310C, turbidity 8.1-11.22 FTU, transparency 61.25-79 cm, current speed 25-36 cm/s, TSS 10.3–16.17 mg/L, TDS 11.17– 16.75 mg/L, depth 17-138 cm, pH 5–5.17, dissolved oxygen 5.47– 6.23 mg/L, BOD5 2.59–3.38 mg/L, nitrate 0.0822-0.1803 mg/L and phosphate 0.4352-0.4823 mg/L. The value of the WQI-NSF index was 62-66, indicates that the river is on moderate condition.Keywords : Kampar River, Water Quality, WQI-NSF, Periphyton